Things that matter ebook Overcoming distraction to pursue a more meaningful life. - Becker, Joshua (2022)
#1 WALL STREET JOURNAL BESTSELLER • Discover practical steps you can take today to live a life focused on things that matter, from the bestselling author of The More of Less and The Minimalist Home . “ Things That Matter points the way to free ourselves from the distractions of everyday life so that we can build the lives we seek to create.”—Gretchen Rubin, author of The Happiness Project Everywhere around you are distractions: That text you respond to quickly, just to get it out of the way. The newest money-making side hustle to cross your mind. The evening spent organizing your overflowing kitchen cupboards. Disruptions are the enemies of a life well lived—both the new distractions of our generation and timeless ones that have existed for centuries. They all add up to make you feel restless, tired, and unfulfilled. They’re keeping you from living with joy, from accomplishing the good that only you can do. But that can change today. In Things That Matter, Joshua Becker uses practical exercises, questions, insights from a nationwide survey, and success stories to give you the motivation you need to   • identify the pursuits that matter most to you • align your dreams with your daily priorities • recognize how money and possessions keep you from happiness • become aware of how others’ opinions of you influence your choices • embrace what you’re truly passionate about instead of planning that next escape • figure out what to do with all those emails, notifications, and pings • let go of past mistakes and debilitating habits   Things That Matter is a book about living well. It’s about overcoming the chatter of a world focused on all the wrong things. It’s about rethinking the common assumptions of today to find satisfaction and fulfillment tomorrow.   How do we get to the end of our lives with minimal regrets? We set aside lesser pursuits to seek lasting meaning. And we discover the joy of doing it every day.